Diagnostic accuracy of contrast-enhanced ultrasound for detecting bland thrombus from inferior vena cava tumor thrombus in patients with renal cell carcinoma - Li,Qiuyang (2020)
ABSTRACT Purpose: To evaluate the role of contrast-enhanced ultrasound (CEUS) in differentiating bland thrombus from tumor thrombus of the inferior vena cava (IVC) in patients with renal cell carcinoma (RCC). Materials and Methods: We retrospectively investigated 30 consecutive patients who underwent robot-assisted radical nephrectomy with IVC thrombectomy and had pathologically confirmed RCC. All patients underwent US and CEUS examination. Two off-line readers observed and recorded thrombus imaging information and enhancement patterns. Sensitivity, specificity, accuracy, positive predictive value and negative predictive value for bland thrombus were assessed. Results: Of the 30 patients, no adverse events occurred during administration of the contrast agent. Early enhancement of the mass within the IVC lumen on CEUS was an indicator of tumor thrombus. Bland thrombus showed no intraluminal flow on CEUS. There were eight (26.7%) patients with bland thrombus, including three level II, two level III, and three level IV. There were three cases with cephalic bland thrombus and five cases with caudal bland thrombus. Three caudal bland thrombi extended to the iliac vein and underwent surgical IVC interruption. Based on no intraluminal flow, for bland thrombus, CEUS had 87.5% sensitivity, 100% specificity, 96.7% accuracy, 100% positive predictive value and 95.6% negative predictive value. Conclusion: Our study demonstrates the potential of CEUS in the differentiation of bland and tumor thrombus of the IVC in patients with RCC. Since CEUS is an effective, inexpensive, and non-invasive method, it could be a reliable tool in the evaluation of IVC thrombus in patients with RCC.